Harmonics Assessment of Distribution Transformer with Photovoltaic Integration and Unbalanced Loads - Muhammad Haziq Mohd Wazir; Mat Said, Dalila; Norazliani Md Sapari; Mohamed Shahriman Mohamed Yunus (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Harmonic distortion is one of the monumental power quality problems in an electrical power system. It frequently originated from non-linear loads generating non-sinusoidal steady state waveforms, which may lead to various undesirable effects on distribution transformers such as increased losses, overheating and lifetime reduction. In previous works, the harmonic current contributions from non-linear loads from consumers have been appointed as the main contributor of harmonic issues in the distribution transformers. However, since the integrations of renewable energy as a distributed generation (DG) have exponentially increasing in recent years, the impact of solar photovoltaic (PV) system implementation into distribution system on amplifying additional harmonic contents also needs to be addressed. Therefore, this paper conducts a comparative analysis of voltage and current harmonic profiles within the distribution transformer in three-phase distribution network and three-phase grid-connected photovoltaic (GCPV) system, with both subjected to supply unbalanced non-linear loads. The simulation is carried out using MATLAB Simulink 2021a software and the results are compared according to standards. As a result, the distribution transformer in the GCPV system is proven to contain higher levels of voltage and current harmonic distortion compared to a normal distribution grid.